LEGAL BASIS OF ORGANIC AGRICULTURE AS AN ECOLOGICAL COMPONENT - Zhmur, Nataliia; Kolonska, Viktoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose provides comprehensive coverage of the essence, advantages, problems, and current trends in the development of organic agriculture in Ukraine and worldwide, taking into account the environmental component. Research methods: documentary analysis and synthesis, cognitive-analytical, as well as systematization and generalization methods were used. The results of the study confirm the environmental advantages of organic agriculture, its important role in combating climate change and the growing global demand for organic products. Ukraine has significant potential in this area, demonstrating positive development dynamics with the support of the state and international partners, despite the difficulties caused by the war. Organic agriculture, based on the principles of health, environmental friendliness, justice and care, contributes to soil health, biodiversity conservation and provides consumers with high-quality and safe products, while stimulating the development of innovative technologies and following modern market trends. Discussion: organic agriculture is an important direction of sustainable development, combining environmental responsibility, production of high-quality and safe products and economic benefits for farmers due to growing consumer demand, especially in international markets, despite certain obstacles, such as the cost of certification and crop risks, support from the state and international partners, as seen in the example of Ukraine, contributes to the expansion of organic agriculture, which has significant potential for soil health, biodiversity conservation and mitigation of environmental problems, and the principles of organic agriculture are the foundation for the development of this industry worldwide.